Analysis Nutritional Status of Pregnant Women, Hemoglobin During Pregnant, Baby Birth Weight, Exclusive Breastfeeding and History of Infectious Disease With Stunting - Febry Mutiariami Dahlan; Ani Yuliani; Putri Azzahroh; Yenny Aulya (International Health Sciences Journal, 2024)
Indonesia is included in the third country with the highest prevalence in the South-East Asia Region (SEAR). The average prevalence of stunting of toddlers in Indonesia in 2005-2017 was 36.4%. The data on stunting toddlers in Tangerang Regency was 23.2%. This study at to determine the factor analysis of stunting at the Caringin Public Health Center, Tangerang Regency in 2021. The type of research used was an analytical observational study with a case control study design. The sample in this study was 75 for each group of cases and controls using simple random sampling technique. The research instrument used a questionnaire for primary data and an MCH handbook for secondary data. Data analysis has been done by a chi square test. Out of 150 respondents, it was found that mothers with a history of CED during pregnancy were 24%, mothers with a history of anemia during pregnancy was 56.7%, a history of LBW was 8.7%, a history of not exclusive breastfeeding was 55.3% , and a history of infectious diseases was 40.7%. Nutritional status of pregnant women (p-value = 0.000, OR = 7.667), HB levels in pregnant women (pvalue = 0.008, OR = 2.563), history of exclusive breastfeeding (pvalue = 0.009, OR = 2.545) were factors associated with stunting. There was a relationship between the nutritional status of pregnant women, HB levels in pregnant women, and a history of exclusive breastfeeding with the incidence of stunting. The factor most related to the incidence of stunting was the nutritional status of pregnant women (OR = 7,667). It is hoped that health workers will further increase the provision of additional food and IEC regarding the importance of FE tablets for pregnant women as a program for improving nutrition for pregnant women